Preparation of multi-layered zinc-hydrogel heterostructures as medical implants

By designing a multi-layer zinc-hydrogel heterostructure, combining bionic cow hoof composite structure and hydrogel material, the ion release and wear problems of existing medical metal materials in the human body are solved, efficient loading and drug carrying are achieved, and completely degraded in the human body, avoiding the risk of secondary surgery.

CN119326956BActive Publication Date: 2025-03-25JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411874697.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

Existing medical metal materials may cause ion release and wear particles after being implanted into the human body, causing allergies and inflammatory reactions, and require secondary surgery to remove, increasing the risk of patients. At the same time, existing zinc materials have shortcomings in structural design and hydrogel combination, which is difficult to meet the clinical needs of femoral implantation.

Method used

A multi-level zinc-hydrogel heterostructure was designed, and zinc powder was printed through bionic cow hoof composite structure model and selection laser melting technology, combined with hydrogel materials, and formed a gradient bionic structure to achieve effective combination of zinc and hydrogel.

Benefits of technology

This structure has efficient load-bearing and drug-carrying capabilities in the human body, and can completely degrade after implantation, avoiding the risk of secondary surgery, and also has good biocompatibility and antibacterial effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326956B_ABST
    Figure CN119326956B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multi-level zinc-hydrogel heterostructure as a medical implant, relates to the technical field of medical implants, and comprises the following steps: step one: completing the establishment of a bionic cow hoof composite structure model based on 3D modeling software, linearly arraying the bionic cow hoof composite structure model three times, and adjusting the porosity of each bionic cow hoof composite structure model in a gradient manner, and finally obtaining a gradient bionic structure model; step two: printing zinc powder into a gradient bionic structure based on a selective laser melting technology; step three: placing the gradient bionic structure in a clean mold, auxiliary filling the prefabricated hydrogel into the gradient bionic structure, and obtaining the multi-level zinc-hydrogel heterostructure after curing; step four: implanting the multi-level zinc-hydrogel heterostructure into a femoral defect, wherein the multi-level zinc-hydrogel heterostructure prepared by the invention can be completely degraded in the human body after implantation, thereby avoiding the risk of secondary postoperative trauma.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical implants, and in particular to a method for preparing a multi-level zinc-hydrogel heterostructure as a medical implant. Background Art

[0002] Currently, most of the medical metal materials used in clinical practice are traditional inert materials such as titanium and titanium alloys, stainless steel and cobalt-based alloys. However, these materials may release harmful ions or wear particles during wear or corrosion after being implanted in the human body, causing allergies and inflammatory reactions. Moreover, these metal materials need to be removed by a second operation after their service, which can easily cause secondary damage to patients. Zinc is a completely degradable metal that has antibacterial properties, helps bone formation, and inhibits osteoclasts from destroying bones. Its standard electrode potential is between magnesium and iron. Compared with other degradable metal materials, it has a moderate degradation rate and does not release hydrogen during the degradation process. It has good application prospects in the field of implantation.

[0003] Additive manufacturing technology is expected to solve the problem that traditional processes are difficult to manufacture complex and fine-structured bone implants. A well-designed scaffold structure is essential for recruiting cells from the surrounding bones, promoting nutrient diffusion and angiogenesis. However, there are relatively few existing studies on additively manufactured zinc, and most of them are based on traditional structures, such as diamond cells, which currently do not have the performance of efficient load-bearing and are difficult to be directly applied to the field of femoral implants. Therefore, the field of femoral implant design needs to explore new structural design methods to meet clinical needs.

[0004] Compared with bone tissue with uniform texture, femoral soft tissue has the characteristics of more complex structure, higher degree of heterogeneity, and wider coverage of mechanical modulus, which makes it very difficult to reconstruct. However, research on the repair of soft tissue defects has just started. Studies have shown that hydrogels can be injected into the affected area percutaneously or by catheter, and gel in situ to achieve rapid filling of the defect site, and then by regulating the degradation of the hydrogel, it can induce the regeneration of surrounding tissue. In addition, the hydrogel itself can carry a variety of drugs to treat the bone defect and further help the patient recover, which is a natural advantage that metal implants do not have. However, the existing hydrogels have poor load-bearing capacity and cannot be used in the process of bone defect healing. Therefore, this is also one of the key properties that need to be improved in the future.

[0005] If zinc and hydrogel are cleverly combined, the performance advantages of the two materials can be combined to make up for the performance gap of a single material, thus realizing a medical implant that can efficiently carry loads and carry drugs. However, existing research lacks means to effectively combine zinc and hydrogel. Summary of the invention

[0006] The present invention aims to solve the shortcomings of the above-mentioned femoral medical bone implant design, and to develop a completely degradable medical implant that can play a load-bearing role in the human body and has good biocompatibility. The present invention designs a gradient bionic structure based on the macro-microstructure of the cow hoof wall in nature, and combines it with a hydrogel with good bone integration and bone inductivity, and combines the hydrogel with the gradient bionic structure to obtain a multi-level zinc-hydrogel heterostructure.

[0007] A method for preparing a multi-layer zinc-hydrogel heterostructure as a medical implant comprises the following steps:

[0008] Step 1: The bionic cow hoof composite structure model is established based on 3D modeling software, the designed bionic cow hoof composite structure model is linearly arrayed three times, and the porosity of each bionic cow hoof composite structure model is adjusted in a gradient manner, and finally a gradient bionic structure model is obtained;

[0009] Step 2: Import the gradient bionic structure model designed in step 1 into the magics software, and print the zinc powder into a gradient bionic structure based on the selective laser melting technology;

[0010] Step 3: placing the gradient biomimetic structure prepared in step 2 in a clean mold, filling the prefabricated hydrogel into the gradient biomimetic structure, and completely solidifying the prefabricated hydrogel by water bath heating or ultraviolet light irradiation according to the selected prefabricated hydrogel material to obtain a multi-level zinc-hydrogel heterogeneous structure;

[0011] Step 4: Implant the multi-layered zinc-hydrogel heterostructure prepared in step 3 into the femoral defect.

[0012] Preferably, the bionic cow hoof composite structure model in step one includes a bionic spiral interlocking structure model and a bionic elliptical chamber structure model.

[0013] Preferably, the bionic spiral interlocking structure model comprises upper units and lower units, and the upper units and the lower units are staggered up and down at an angle of 90°.

[0014] Preferably, the upper unit and the lower unit have the same structure, and the upper unit is obtained by a planar circular array of four bionic spiral interlocking structure unit cell models with an interlaced angle of 90°.

[0015] Preferably, each bionic spiral interlocking structure unit cell model is formed by stacking a plurality of stepped plates, wherein two adjacent stepped plates do not fit together under no load, and when loaded, each adjacent stepped plate partially overlaps to further dissipate the force.

[0016] Preferably, the bionic elliptical chamber structure model is obtained by linearly arraying the bionic elliptical chamber structure unit cells along the X-axis, the Y-axis and the Z-axis respectively.

[0017] Preferably, the bionic elliptical chamber structure unit cell is obtained by mirroring two bionic elliptical chamber structure unit cell models.

[0018] Preferably, the unit cell model of the bionic elliptical chamber structure is obtained by a plane circular array of two elliptical chamber convex plates with the center R as the rotation point and an interlaced angle of 90°.

[0019] Preferably, the printing parameters used in the selective laser melting technology in step 2 are: laser power 70w, scanning speed 500mm / s, scanning spacing 80μm, and scanning layer thickness 40μm.

[0020] Beneficial effects of the present invention:

[0021] The bionic cow hoof composite structure designed by the present invention is relatively novel. The bionic cow hoof composite structure is constructed based on the macro-microstructure of the cow hoof wall in nature. The designed bionic cow hoof composite structure has the performance of efficient load-bearing and stable deformation, and at the same time takes advantage of the synergistic energy absorption effect of the multifunctional characteristics of natural organisms, solving the problems of insufficient load-bearing and easy instability of traditional medical bone implant structures.

[0022] The multi-level zinc-hydrogel heterogeneous structure prepared by the present invention achieves a breakthrough in the rigid-flexible coupling of the hydrogel and the gradient bionic structure, and realizes the combination of the drug-carrying property of the hydrogel and the load-bearing and energy-absorbing advantages of the gradient bionic structure, and has both excellent mechanical properties and the effect of inhibiting bacteria and eliminating inflammation.

[0023] The multi-level zinc-hydrogel heterogeneous structure prepared by the present invention can be completely degraded in the human body after implantation, thereby avoiding the risk of secondary postoperative trauma. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the present invention;

[0025] Figure 2 It is a schematic diagram of the patient's recovery process after implantation of femoral defect tissue in the present invention;

[0026] Figure 3 It is a flow chart of the design of the bionic spiral interlocking structure model;

[0027] Figure 4 It is a flow chart of the design of the bionic elliptical chamber structure model;

[0028] Figure 5 This is an enlarged view of the local structure of the gradient bionic structure implanted into the femoral defect tissue;

[0029] Figure 6 The multi-layered zinc-hydrogel heterostructure is prepared by a water bath heating method;

[0030] Figure 7 It is a multi-layered zinc-hydrogel heterostructure prepared by ultraviolet light irradiation;

[0031] In the figure:

[0032] 1: Bionic cow hoof composite structure model; 10: Bionic spiral interlocking structure model; 100: Bionic spiral interlocking structure unit cell model; 11: Bionic elliptical chamber structure model; 110: Bionic elliptical chamber structure unit cell model; 2: Gradient bionic structure model; 3: Multi-layer zinc-hydrogel heterostructure. DETAILED DESCRIPTION

[0033] See also Figures 1 to 7 As shown, the preparation method of the multi-layer zinc-hydrogel heterostructure as a medical implant comprises the following steps:

[0034] Step 1: Based on the 3D modeling software solidworks, the bionic cow hoof composite structure model 1 is established, the designed bionic cow hoof composite structure model 1 is linearly arrayed three times, and the porosity of each bionic cow hoof composite structure model 1 is adjusted in a gradient manner, and finally a gradient bionic structure model 2 is obtained;

[0035] Step 2: Convert the gradient bionic structure model 2 designed in step 1 into an STL format file and import it into the magics software, and print the zinc powder into a gradient bionic structure based on the selective laser melting technology;

[0036] Step 3: placing the gradient biomimetic structure prepared in step 2 in a clean mold, filling the prefabricated hydrogel into the gradient biomimetic structure, and completely solidifying the prefabricated hydrogel by water bath heating or ultraviolet light irradiation according to the selected prefabricated hydrogel material to obtain a multi-level zinc-hydrogel heterostructure 3;

[0037] Step 4: Implant the multi-layered zinc-hydrogel heterostructure 3 prepared in step 3 into the femoral defect.

[0038] For further information, see Figure 1 As shown, the bionic cow hoof composite structure model 1 in the step one includes a bionic spiral interlocking structure model 10 and a bionic elliptical chamber structure model 11; the bionic cow hoof composite structure model 1 is constructed based on the bionic features extracted from the macro-microscopic characterization of the cow hoof wall, the bionic spiral interlocking structure model 10 is constructed based on the layered interlocking structure of the outer layer of the cow hoof wall keratin, and the bionic elliptical chamber structure model 11 is constructed based on the horn core porous structure inside the cow hoof wall keratin.

[0039] For further information, see Figure 1 and Figure 3As shown, the bionic spiral interlocking structure model 10 includes upper units and lower units, and the upper units and the lower units are staggered up and down with an interlaced angle of 90°.

[0040] For further information, see Figure 1 and Figure 3 As shown, the upper unit and the lower unit have the same structure, and the upper unit is obtained by a plane circular array of four bionic spiral interlocking structure unit cell models 100 with an interlaced angle of 90°.

[0041] For further information, see Figure 3 As shown, each bionic spiral interlocking structure unit cell model 100 is composed of a plurality of stacked stepped plates. Two adjacent stepped plates do not fit together (there is a gap) under no load, and when there is a load, each adjacent stepped plate will partially overlap to further dissipate the force and stabilize the deformation.

[0042] For further information, see Figure 3 As shown, the present invention exemplifies a design method of a bionic spiral interlocking structure model 10, which includes the following contents:

[0043] First, the sketch optimization is performed based on one-third of an XY plane of a simple cubic structure. The intersection points of the second truss longitudinal beam and the three truss cross beams are points H, I, and J. The intersection points of the first truss longitudinal beam and the four truss cross beams are points A, B, C, and D. The trusses are extended from points H, I, and J to the midpoints E, F, and G of AB, BC, and CD, respectively. The step-like sketches HEI, IFJ, and FJG are obtained, where a uniform rotation angle α (90°> α > 30°) is used to regulate the position of the step-like sketch to ensure that the lateral and longitudinal dimensions of the bionic spiral interlocking structure model 10 remain a and c after the porosity changes. Secondly, the optimized step-like sketch is linearly arrayed twice along the X direction of the XY plane with a horizontal dimension of a / 3 to obtain a step-like sketch group. After the array is completed, the step-like sketch group is subjected to thin-wall stretching as a whole, and the stretching dimension is b. Finally, a bionic spiral interlocking structure unit cell model 100 with a dimension of a×b×c is obtained. The bionic spiral interlocking structure unit cell model 100 is circularly arrayed four times with a staggered angle of 90°. After the circular array is completed, it can be found that the four bionic spiral interlocking structure unit cell models 100 are locked with each other, which improves the stability of the upper unit. Finally, the upper unit obtained by the four circular arrays is moved and copied along the Z axis with a displacement of size c, and then the copied upper unit is rotated 90° along the Z axis to obtain the lower unit. Finally, the eight bionic spiral interlocking structure unit cell models 100 are combined to obtain the bionic spiral interlocking structure model 10. The size of the bionic spiral interlocking structure model 10 is (a+b)×(a+b)×2c (corresponding to the X-axis-Y-axis-Z-axis, a and b are the same).

[0044] For further information, see Figure 4 As shown, the bionic elliptical chamber structure model 11 is obtained by linearly arraying the bionic elliptical chamber structure cells along the X-axis, the Y-axis and the Z-axis respectively.

[0045] For further information, see Figure 4 As shown, the bionic elliptical chamber structure unit cell is obtained by mirroring two bionic elliptical chamber structure unit cell models 110 .

[0046] For further information, see Figure 4 As shown, the bionic elliptical chamber structure unit cell model 110 is obtained by two elliptical chamber convex plates with the center R as the rotation point and a plane circular array with an interlaced angle of 90°.

[0047] For further information, see Figure 4 As shown, the present invention exemplifies a design method of a bionic elliptical chamber structure model 11, which includes the following contents:

[0048] First, the structure is optimized based on the rectangular frame structure, and the curvature is extended based on the face center R of the above part of the truss. The extension points are located at the midpoints P and Q of the two truss longitudinal beams LM and the truss longitudinal beam NO, respectively. Secondly, the optimized elliptical cavity convex plate is arrayed once with the face center R as the rotation point. After the circumferential array, the bionic elliptical cavity structure unit cell model 110 that interacts with the face center R is obtained. Then, the bionic elliptical cavity structure unit cell model 110 is mirrored to obtain the bionic elliptical cavity structure unit cell. The size of the bionic elliptical cavity structure unit cell is a×b×c (corresponding to the X-axis-Y-axis-Z-axis). Finally, the bionic elliptical cavity structure unit cell is linearly arrayed once along the X-axis, Y-axis and Z-axis with the size a, b and c respectively to obtain the bionic elliptical cavity structure model 11. The size of the bionic elliptical cavity structure model 11 is 2a×2b×2c.

[0049] For further information, see Figure 1 , Figure 3 and Figure 4 As shown, the gradient bionic structure model 2 in step 1 is composed of three bionic cow hoof composite structure models 1 with different porosities. The porosity of the gradient bionic structure model 2 presents a negative gradient from bottom to top (75%-60%-45%). This porosity range has been proven to be suitable for bone implants, and the negative gradient strategy has been proven to be effective in reducing vibration and dissipating impact energy. The adjustment of the porosity of the bionic spiral interlocking structure model 10 depends on the wall thickness characteristic parameter T and the angle parameter α of the bionic spiral interlocking structure unit cell model 100, respectively. The adjustment of the porosity of the bionic elliptical chamber structure model 11 depends on the wall thickness characteristic parameter T of the bionic elliptical chamber structure unit cell model 110. The wall thickness of the bionic spiral interlocking structure unit cell model 100 and the bionic elliptical chamber structure unit cell model 110 should be consistent to facilitate the adjustment of the overall porosity.

[0050] Furthermore, the printing parameters used in the selective laser melting technology in step 2 are laser power 70W, scanning speed 500mm / s, scanning spacing 80μm, and scanning layer thickness 40μm. The printing parameters are the optimal solutions obtained based on orthogonal experiments in existing research.

[0051] For further information, see Figure 1 As shown, in step 3, the specific method and proportion of using a water bath heating method to assist in filling the prefabricated hydrogel material into the gradient biomimetic structure to obtain the multi-level zinc-hydrogel heterostructure 3 are as follows:

[0052] First, 1.0 g of carboxymethyl chitosan was added to a beaker containing 10 mL of deionized water and stirred into a liquid at room temperature. Subsequently, 1.80 g of acrylamide monomer was slowly added to the mixture and continued to stir for 30 min. At this stage, the required drugs, such as VEGF (vascular endothelial growth factor) and PDGF-BB (recombinant human platelet-derived growth factor-BB) were added. Next, 18.0 mg of APS (ammonium persulfate) and 1.80 mg of MBA (N,N-methylenebisacrylamide) were added and stirred evenly. The obtained mixed solution was then placed in the gradient bionic structure through a 1 ml syringe. The mold was then shaken appropriately to ensure that the prefabricated liquid hydrogel could fully fill the pores of the gradient bionic structure. Finally, the mold was placed in a 60 ° C water bath for 3 h to obtain a multi-layer zinc-hydrogel heterostructure 3, as shown in FIG. Figure 6 shown.

[0053] For further information, see Figure 1 As shown, in the step 3, the specific method and proportion of using ultraviolet light irradiation to assist in filling the prefabricated hydrogel material into the gradient biomimetic structure to obtain the multi-level zinc-hydrogel heterostructure 3 are as follows:

[0054] First, 1.0 g of carboxymethyl chitosan was added to a beaker containing 10 mL of deionized water and stirred at room temperature to form a liquid. Then, 1.80 g of acrylamide monomer was slowly added to the mixture and stirred for 30 min. At this stage, drugs that can be used for recovery, such as VEGF (vascular endothelial growth factor) and PDGF-BB (recombinant human platelet-derived growth factor-BB) were added. In this process, a reference agent suitable for photocrosslinking reaction, such as methyl phenyl acetone photoinitiator 2959, was added. Subsequently, 18.0 mg of APS (ammonium persulfate) and 1.80 mg of MBA (N, N-methylenebisacrylamide) were added in sequence and stirred evenly. Then, the obtained mixed solution was placed in the gradient bionic structure through a 1 ml syringe. Then, the mold was properly shaken to ensure that the prefabricated liquid hydrogel could fully fill the pores of the gradient bionic structure. Finally, the mold was irradiated under ultraviolet light for about 30 min to obtain a multi-layer zinc-hydrogel heterostructure 3, as shown in FIG. Figure 7 shown.

[0055] See also Figure 1 As shown, when facing impact, the bionic spiral interlocking structure (the solid structure obtained by printing the bionic spiral interlocking structure model 10) is used for the main load bearing, while the bionic elliptical chamber structure (the solid structure obtained by printing the bionic elliptical chamber structure model 11) is used for transition and dissipation of part of the impact energy. The bionic spiral interlocking structure is combined with the bionic elliptical chamber structure to further improve the vibration reduction performance. In addition, corresponding to the uneven force caused by the distribution of trabeculae in the femur, a negative gradient array strategy is established on this basis (such as Figure 5as shown).

[0056] See also Figure 1 As shown in the figure, existing studies have confirmed that the hierarchical structure of bionic prototypes such as cow hoof walls in nature is one of the reasons for their excellent impact resistance, and this type of mechanism of synergistic coupling of energy absorption and load bearing by multiple bionic features is also widely present in nature. The cow hoof wall with α-keratin can be regarded as a composite material composed of a layered structure and a microtubule structure. From a macroscopic perspective, the outer layer of the cow hoof wall can form multiple interlocking interfaces, which has the same effect as a multi-stage deceleration structure. And the arrangement angle of the layer changes with the deflection from 0° to 90°. In addition, regarding the reinforcement mechanism of biological hoof walls in nature, it has been proved that the layered structure (with different arrangements) plays a role in stress dispersion and energy absorption. In addition, the microtubules with medullary cavities observed at the microscopic perspective of the outer layer have been confirmed to have the effect of synergistic energy absorption during the load-bearing process. Therefore, we chose to establish a bionic spiral interlocking structure based on the macroscopic interlayer morphology and a bionic elliptical chamber structure based on the microscopic medullary tubule morphology.

[0057] See also Figure 1 and Figure 5 As shown in the figure, since the microtubule structure in the hoof wall is surrounded by the inter-tube material, a special interlocking structure will be formed at the interface, which has been proven to effectively enhance the bonding strength of the interface. Therefore, based on the mechanical coupling strategy, we coupled the bionic spiral interlocking structure with the bionic elliptical chamber structure at the interface connection to prepare a bionic hoof composite structure. When facing impact, the bionic spiral interlocking structure will mainly play a load-bearing effect, while the bionic elliptical chamber structure will mainly play a role in stable deformation, transition and dissipation of a small amount of impact energy. This combination strategy also avoids the phenomenon of insufficient load-bearing or easy stress concentration leading to instability of a single structure. In addition, the negative gradient array strategy has been proven to be more suitable for resisting impact deformation. At the same time, in order to adapt to the implantation characteristics of uneven distribution of trabeculae, we set up a negative gradient scheme. The gradient design is divided into three layers. The wall thickness is adjusted according to the different porosities. The wall thickness of the gradient bionic structure gradually increases from bottom to top, indirectly forming a loose area, a transition area, and a dense area.

[0058] See also Figure 1 and Figure 2As shown in the figure, we placed the prepared multi-layer zinc-hydrogel heterostructure 3 in the femoral defect to analyze how the multi-layer zinc-hydrogel heterostructure 3 exerts its biocompatibility after implantation; first, in the early stage of implantation, the hydrogel began to degrade, and the drug components it contained played a role. VEGF can stimulate the recruitment of blood vessels and osteoclasts, and promote cartilage absorption at the repair site during the periosteal cartilage ossification stage, while PDGF-BB drug components can promote angiogenesis. In this process, the gradient bionic structure was exposed, and partial degradation also occurred, but the degree of degradation was slower than that of the hydrogel. Secondly, in the middle stage of implantation, the hydrogel was completely degraded, the drug mission it carried had been completed, and the gradient bionic structure was completely exposed. At this time, the service life has not yet ended, and the gradient bionic structure still plays a bearing and supporting role. At the same time, with the Zn 2+ As the bone is generated, bone cells grow into the gradient bionic structure, and the two gradually form an interlocking trend. Finally, it reaches the late stage of implantation, when the trabeculae grow well, the gradient bionic structure completes its service mission, and then completely degrades in the human body environment without the need for secondary removal.

[0059] It is worth mentioning that the time and duration of the selected hydrogel drug release can be optimized by adjusting the proportion of components and the gelation method. Similarly, the service condition and degradation speed of the gradient bionic structure can be further controlled by adjusting parameters and material composition (this is the existing technology and will not be elaborated here).

Claims

1. A method for preparing a multi-layer zinc-hydrogel heterostructure as a medical implant, characterized in that: The steps include: Step 1: Based on 3D modeling software, the bionic cow hoof composite structure model (1) is established, the designed bionic cow hoof composite structure model (1) is linearly arrayed three times, and the porosity of each bionic cow hoof composite structure model (1) is adjusted in a gradient manner, and finally a gradient bionic structure model (2) is obtained; Step 2: Import the gradient bionic structure model (2) designed in step 1 into the magics software, and print the zinc powder into a gradient bionic structure based on the selective laser melting technology; Step 3: placing the gradient biomimetic structure prepared in step 2 in a clean mold, filling the prefabricated hydrogel into the gradient biomimetic structure, and completely solidifying the prefabricated hydrogel by water bath heating or ultraviolet light irradiation according to the selected prefabricated hydrogel material to obtain a multi-level zinc-hydrogel heterogeneous structure (3); Step 4: implanting the multi-layered zinc-hydrogel heterostructure (3) prepared in step 3 into the femoral defect; The bionic cow hoof composite structure model (1) in step 1 comprises a bionic spiral interlocking structure model (10) and a bionic elliptical chamber structure model (11); The bionic spiral interlocking structure model (10) includes an upper unit and a lower unit, and the upper unit and the lower unit are staggered up and down at an angle of 90°; The upper unit and the lower unit have the same structure. The upper unit is obtained by a plane circular array of four bionic spiral interlocking structure unit cell models (100) with an interlaced angle of 90°; Each bionic spiral interlocking structure unit cell model (100) is formed by stacking a plurality of stepped plates, wherein two adjacent stepped plates do not fit together when no load is applied, and when a load is applied, each adjacent stepped plate partially overlaps to further dissipate the applied force; The bionic elliptical chamber structure model (11) is obtained by linearly arraying the bionic elliptical chamber structure unit cells along the X-axis, Y-axis and Z-axis respectively; The unit cell of the bionic elliptical chamber structure is obtained by mirroring two unit cell models of the bionic elliptical chamber structure (110); The unit cell model (110) of the bionic elliptical chamber structure is obtained by a plane circular array of two elliptical chamber convex plates with the center R as the rotation point and an interlaced angle of 90°.

2. The method for preparing the multi-level zinc-hydrogel heterostructure as a medical implant according to claim 1, characterized in that: The printing parameters used in the selective laser melting technology in step 2 are: laser power 70w, scanning speed 500mm / s, scanning spacing 80μm, and scanning layer thickness 40μm.

Citation Information

Patent Citations

  • Expandable slide and lock stent

    CN102843997A

  • Enossal single tooth implant with twisting restraint

    CN1062834A